2021
DOI: 10.1108/srj-07-2020-0298
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relative role of CSR activity and service experience on cruise customers’ behavior

Abstract: Purpose In the service industry, corporate social responsibility (CSR) is considered a strategic valuable resource. Although previous studies emphasized CSR activities in the service industry, a limited number of studies have examined the combined effect with the service experience. Thus, this study aims to examine the potential antecedents of cruise customers’ positive responses toward the cruise company. Design/methodology/approach The proposed model includes CSR activities, service experiences, satisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 88 publications
(95 reference statements)
1
2
0
1
Order By: Relevance
“…Moreover, our results were in line with most previous research, confirming that loyalty had a positive relationship with a firm's CSR activity in general [34,[38][39][40]. Particularly, ref.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, our results were in line with most previous research, confirming that loyalty had a positive relationship with a firm's CSR activity in general [34,[38][39][40]. Particularly, ref.…”
Section: Discussionsupporting
confidence: 92%
“…Even though loyalty has been examined substantially in the marketing literature, it has received a finite amount of attention when studying consumers' perspectives toward hiring PWDs. The literature showed contrasting results when addressing the effect of CSR on loyalty, as most studies granted a significant positive effect of CSR on customers' loyalty [39,40], supporting earlier research suggesting a positive relationship between the two variables [34]. Other research revealed a positive effect of CSR on customer's retention that was caused by increased loyalty for those customers [41].…”
Section: Loyaltymentioning
confidence: 84%
“…Ecologically sound management practices are increasingly vital, given global concerns over pollution and climate change [4,5]. This movement toward greener operations, coupled with efforts to enhance CSR, improves both corporation image and the fulfillment of sustainability goals, demonstrating reciprocity between corporations and their stakeholders [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…De acuerdo con las publicaciones disponibles, se puede apreciar que el logro de la RSC se reconoce a partir de diferentes aspectos: la prestación de un servicio de calidad acorde con los requerimientos de los clientes (Afzali y Kim, 2021;Ahn y Lu, 2021;Akbari et al, 2020), el responder a las demandas de conservación ambiental (Adomako y Nguyen, 2020;Alda, 2019) y la contribución al desarrollo del territorio, en sus diferentes escalas de análisis (Bhatia y Makkar, 2020;Boğan et al, 2020). De igual modo, se pudo apreciar que existe un grupo de variables en la organización cuyo comportamiento condiciona el grado de madurez de la RSC, entre estos destacan: el liderazgo que ejerce la directiva y la forma en que este promueve un comportamiento socialmente responsable (Aftab et al, 2021;Bardos et al, 2020).…”
Section: Introducción Y Estado De La Cuestiónunclassified